KADAR ESTROGEN DAN PROFIL OVIDUK PUYUH (Coturnix coturnix japonica) SETELAH PEMBERIAN CAHAYA MONOKROMATIK - Kasiyati, Kasiyati; Kusumorini, Nastiti; Maheshwari, Hera; Manalu, Wasmen (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
Light plays an important role in the avian life. The present study was designed to evaluate the effects of monochromatic light on serum estrogen concentrations and profile the oviduct, that were the length and weight of the oviduct in the quail. Two hundred and seventy quails were divided into nine treatments of light, with ten replications and three quails in each replication. The treatments were without light,  controls  with 15 and 25 W, red, green, and blue lights with intensities of  15 and 25 lux. Control  treatment used incandescent bulb.  The red,  green,  and  blue lights  were  provided  by   light emitting   diodes  (LED). All lights   treatment   were   given   for   14 h  daily,   started from 17.00 to 07.00. Parameters   measured  were  serum estrogen  concentrations, and  weights  and  lengths  of   the  oviduct  on  weeks 5,  7,  and  9.  Quails   exposed  to  monochromatic   light had  higher  serum  estrogen  concentrations (P<0,05). Quails  exposed to monochromatic light had  better  weights  and  lenghts of  the  oviduct  development. Blue light could be used to increase serum estrogen concentrations and stimulate shell gland development.